Mortality Crisis in the South Andean: Moquegua, Tacna, Altos de Arica and Tarapacá (1754-1820); [Crisis de Mortalidad en el Sur Andino: Moquegua, Tacna, Altos de Arica y Tarapacá (1754-1820)*] - Inostroza-Ponce, X (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2022)
Through the death records’ analysis of Moquegua, Tacna, Altos de Arica and Tarapacá settlements, it is aimed to observe the close relationship that exists between epidemics, natural (primarily climatic) and social phenomena, as well as evaluate their impact on mortality. The similarities detected between the studied localities and the regional context, especially in terms of the effects caused by certain natural phenomena and other epidemics on the population, are going to account for both the spaces proximity and the narrow relation among urban and rural spaces in this vast territory belonging to the Andean space of the Arica-Potosí axis. © 2022 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.